ANALISIS IMPLEMENTASI PENGINTEGRASIAN PELAYANAN KESEHATAN TRADISIONAL DI PUSKESMAS HALMAHERA KOTA SEMARANG - Annisa Rahmawati; Sutopo Patria Jati; Ayun Sriatmi (Jurnal Kesehatan Masyarakat (Undip), 2016)
Government  wants to integrate traditional health care in the healthcare system, then some of the regulatory framework published. Including Permenkes no. 1109 tahun 2007, Kepmenkes no. 121 tahun 2008 and PP no 103 tahun 2014. The Government is also targeting the implementation of the integration of traditional health care in the Ministry of Health Strategic Plan 2015 - 2019, with indicators 15% Health Center organizes traditional medicine at 2015. In Semarang until mid 2015 only 3%(1) Public health center implement the integration of traditional health services which is Halmahera Health center.This study aimed to analyze the implementation of the integration of traditional health services in Puskesmas Halmahera Semarang. This research is a descriptive study using a qualitative approach. Collecting data with in-depth interviews. The informants are health workers implementing the integration of traditional health services in Halmahera Health center, Section Head of Pharmaceuticals, Food Beverage and Health Supplies, Head of Health Services Semarang City Health Office, Pharmaceutical and Food Supervisory Staff BPOM.Research shows the Halmahera health centers and DKK do not yet know the policy indicators, Nurses do not have SBRTPKA (Proof of Registration Complementary Alternative Healers)   and STTPKA (Letter of Complementary Alternative Healers Task Force) because of they does not know how to get SBRTPKA and STTPKA. There is no separate room for acupressure, there is no allocation funds for the program, they do not have Standard Operating Procedures. There are to high workload for nurse, doctors rarely suggest acupressure. Semarang do not have regulatory about alternative complementary medicine. The society has the will to utilize traditional health care, but they have objections about the cost of traditional health care utilization